Design-thinking integration in cultural project planning: bridging theory and practice - Zhang, Shiyong; Vate-U-Lan, Poonsri; Sivapirunthep, Panneepa (Institute of Advanced Engineering and Science, 2025)
This qualitative study aimed to bridge the gap between theoretical knowledge and practical skills by developing a design thinking-based innovative pedagogy for creative planning of cultural projects at Shanxi University of Finance and Economics (SUFE). The discover, define, design, develop, and deploy (5Ds) model, an innovative pedagogy grounded in design thinking, was designed with five phases. After evaluation by five cultural project planning experts, the model was refined to align closely with pedagogical objectives. Three primary research instruments were employed: a theoretically derived framework, a meticulously designed lesson plan, and an achievement test. Contextually tailored to Chinese culture, each phase was symbolized by a Chinese lantern, signifying prosperity and the intended positive outcomes of the pedagogy. The phases comprised: i) discover, where consumer needs were analyzed; ii) define, identifying problems and setting objectives; iii) design, focusing on idea generation; iv) develop, involving prototyping, implementation, and revisions; and v) deploy, for final product testing and market introduction. This culturally resonant pedagogical framework supports a comprehensive approach to teaching cultural project planning, fostering innovation, and practical application. Through symbolic integration, the 5Ds model aligns with educational goals while encouraging Chinese students to embrace innovation. Outcomes indicate enhanced teaching quality and instructional effectiveness, addressing existing educational challenges.